(untitled) (Journal of the College of Basic Education, 2023)
By virtue of its strategic location close to the theater of military operations, and its association with France, Morocco contributed to the Second World War 1939_1945 on the side of the Allied countries. Sultan Muhammad bin Yusuf (Mohammed V) made an appeal to the Moroccans, in which he called for Morocco’s full and unreserved support for France in this war, hoping that The victorious countries grant independence to Morocco after the end of the war. Morocco’s logistical contribution was of great importance to the Allied countries in order to block the road to Germany in the event of its attempt to occupy the Mediterranean basin. As for its military contribution, Moroccan soldiers received intensive military training by French officers, and the latter was trained by corps of shooters and anti-aircraft artillerymen. He participated. Moroccan soldiers in the liberation of the territory of France and Belgium and penetrated into German territory. In addition to Morocco’s economic contribution and providing France with animal and agricultural products, and the establishment of funds for financial and in-kind donations, and mining wealth became at the disposal of France and its allies, which negatively affected the Moroccan economy, and after the end of the war, the allied countries did not fulfill their promises to Sultan Muhammad V and the Moroccan people.